A HEURISTIC FIXED LIMIT BAYESIAN P CHART - Abooie, MH; Nayeri, M Amin (The South African Journal of Industrial Engineering, 2009)
The paper proposes an efficient approach to detecting an increase in the fraction of nonconforming